Anti-Chinese protests in Turkey : relations with China under test - Dorsey James M. (2015)
Protests in Turkey against alleged repression of Muslim Uighurs in Xinjiang have put China’s sensitive relationships with the Muslim world to the test. The protests raise the spectre of China’s restrictive policy towards the Uighurs muddying relations with other Muslim nations as well.